Design of Rabin-like cryptosystem without decryption failure - Asbullah, Muhammad Asyraf; Kamel Ariffin, Muhammad Rezal (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
In this work, we design a new, efficient and practical Rabin-like cryptosystem without using the Jacobi symbol, redundancy in the message and avoiding the demands of extra information for finding the correct plaintext. Decryption outputs a unique plaintext without any decryption failure. In addition, decryption only requires a single prime. Furthermore, the decryption procedure only computes a single modular exponentiation instead of two modular exponentiation executed by other Rabin variants. As a result, this reduces the computational effort during the decryption process. Moreover the Novak’s side channel attack is impractical over the proposed Rabin-like cryptosystem. In parallel, we prove that the Rabin-p cryptosystem is indeed as intractable as the integer factorization problem.